PENGUKURAN KUALITAS AUDIT: SEBUAH ESAI - WIDIASTUTY, ERNA; FEBRIANTO, RAHMAT (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 2 (2010), 2010)
This paper discusses audit quality issue. The issue becomes importantafter the fall of Andersen accounting firm, which is one of the biggestinternational accounting firms. To define audit quality, the author uses twoprimary dimensions from DeAngelo (1981b): competency and independency. Butunlike DeAngelo’s market approach, the author uses actual competency andindependency.Another issue is unit of analysis. Researchers should separate the workquality of an accounting firm and that of an auditor. This separation implies thatif competency is assumed to be constant, auditors working in big and smallaccounting firms are different only in terms of independency.It does not mean that this paper is complete enough to support auditingresearches to understand the whole audit quality measurement problem. Thepaper is expected to guide future researches examining audit quality byconsidering weaknesses of the existing measurement tools.
Keywords: audit quality, competency, independency, measurement.